KEUNGGULAN PENERAPAN FUZZY PADA PENYELESAIAN PENJADWALAN PROYEK - Sapti Wahyuningsih; Aprilia Hamida Mashuri (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2021)
Project scheduling is an activity to determine the duration of each activity on the project so that the project can be completed in an optimal time. Network flow in the application of graph theory is the theoretical basis used to complete the project schedule. Some methods that can be used to complete scheduling are Gantt, CPM (Critical Path Method), PERT method (Project Evaluation and Review Technique), and fuzzy application. This article will examine the advantages of applying fuzzy after project scheduling. In the PERT and CPM methods, there are forward computation, backward computation, and float or slack calculations, while scheduling using fuzzy calculations is carried out in one step, namely, the calculation starts from the 'start' node. and move to the 'end. In the application of fuzzy, the degree of membership is discussed to model uncertainty so that the value of the probability of reaching the target is represented in the form of a curve so that the tolerance for project completion can be determined if something unplanned occurs, such as changes in weather/rain or other constraints. The final result of the analysis of fuzzy calculations can be obtained as the most likely value, namely the value with the degree of membership equal to 1 to be the solution in the search for the fastest completion time of a project.